Structural and magnetic transitions of CoFeMnNiAl high-entropy alloys caused by composition and annealing. (October 2021) - Zuo, Tingting; Cheng, Yongqiang; Chen, Peiyong; Gao, Zhaoshun; Zhang, Yong; Liaw, Peter K.
Abstract: Tailoring magnetic behavior by composition and annealing is an effective way. The phase transition from the face-centered-cubic (FCC) to B2 structure influenced by the Al content on the CoFeMnNiAlx alloys leads to the enhanced magnetization. However, the excessive Al addition in the B2-structured alloys impairs the magnetization. The phase transformation caused by annealing also indicates that the saturation magnetization of the alloy depends on the volume fraction of the B2 phase, and a higher content of the B2 phase is beneficial to the large saturation magnetization. Ab initio calculations are used to explain the magnetic behavior of the present HEAs and the effects of phase structures on magnetic characteristics. The phase stability of the CoFeMnNiAlx alloy is thoroughly studied by both the existing phase-formation empirical criteria and annealing. The existing empirical criteria used to predict the phase formation are not universal. However, combining the ΔHmix -δ relation and the φ value, whether the single disordered solid-solution phase is formed can be preliminarily predicted. Highlights: CoFeMnNiAlx alloys are designed based on the high entropy effect. The saturation magnetization of the alloys is related with the phase structure. Annealing induced increment of B2 phase increases the saturation magnetization. The existing phase-formation empirical criteria is evaluated.